STABLISHMENT OF CRITICAL MONTHS TO IRRIGATED AGRICULTURE FROM A WATER BALANCE STUDY - Silva Junior, J. F.; Hernandez, F. B. T.; Silva, I. P. F.; Reis, L. S.; Teixeira, A. H. de C. (Revista Brasileira de Engenharia de Biossistemas, 2018)
The climatic water balance monitors stored soil water from precipitation, atmospheric demand, potential evapotranspiration to supply crop water requirement. It is an important management tool for water resource essential for irrigation projects due to provide information relative to precipitation frequency and volume as well as water deficit timing and season that should be supplied with irrigation or precipitation, allowing the crop achieve potential yields. The irrigation systems have increasingly over years, especially to center pivot irrigation systems that expanded in an annual average of 104.000 ha. Nevertheless, farmers have been using the irrigation systems without an accurate irrigation project and a professional that could calculate the water balance necessary to supply the crop demand using the appropriate local environmental conditions. Therefore, the objective of this study was to determine the critical months to supply the required water necessary to the crop achieve great yields in São Paulo Northwest area from a water balance study. The data analysis demonstrated that August, September and October are the critical months due to presented water deficit of 114, 49 and 81 mm, respectively and increased the evapotranspiration average values.